2009
DOI: 10.16997/jdd.78
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Genomics (PHG) and Public Participation: Points to Consider

Abstract: Large-scale population biobanks, which aim to collect biological tissues, personal health information, and genomic data, are being introduced worldwide with the promise of increasing knowledge on chronic diseases such as diabetes and heart disease. Experts recognize the need for public participation to address the many social, legal and ethical complexities raised by the introduction of biobanks for public health research. However many researchers and decision makers struggle with how to promote public partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the course of our investigation, we realized, on the one hand, that CEPs reflect the challenges of the usually addressed dichotomy between experts and lays. As analyses in science and technology studies (STS) have shown (Avard et al, 2009;Irwin, 2006), common public engagement models are conceived in a one-way procedure in which experts deliver the knowledge to the citizens, who can interact with them by asking about, arguing, and contesting it. "Upstream engagement" of publics at early stages of technological developments has been addressed in public policy discourses (Burri, 2009: 498) and was realized in consensus conferences and citizens' panels (Rose et al, 2017;Rowe and Frewer, 2005).…”
Section: Engagement Of Knowledges In Public Discourses In Austrian Bimentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of our investigation, we realized, on the one hand, that CEPs reflect the challenges of the usually addressed dichotomy between experts and lays. As analyses in science and technology studies (STS) have shown (Avard et al, 2009;Irwin, 2006), common public engagement models are conceived in a one-way procedure in which experts deliver the knowledge to the citizens, who can interact with them by asking about, arguing, and contesting it. "Upstream engagement" of publics at early stages of technological developments has been addressed in public policy discourses (Burri, 2009: 498) and was realized in consensus conferences and citizens' panels (Rose et al, 2017;Rowe and Frewer, 2005).…”
Section: Engagement Of Knowledges In Public Discourses In Austrian Bimentioning
confidence: 99%
“…Inputs were given by expert presentations that provided insights into the practice of biobanking, informed about the current legal situation, and discussed ethical considerations. Following this information phase, citizens had the opportunity to ask questions as well as introduce and discuss their own ideas, opinions, and attitudes with the practitioners in order to motivate active participation and to engage the public (Avard et al, 2009). After a break, small groups of citizens discussed -in the absence of the professional experts -key questions concerning ELSI in biobanking.…”
Section: Conducting and Challenging Citizen-expert Panelsmentioning
confidence: 99%
“…Indeed, evidence is emerging on the beneficial impact of public engagement strategies [18], which are seen to empower members of the public to play a role in shaping current or future research or governance practices [19]. Given this, calls for engagement with stakeholders and the wider public specifically in the area of genomic technologies more broadly [1,[20][21][22] and particularly in the forensics arena [23][24][25][26], have been particularly prominent, while other authors have called for caution about engagement strategies and practices that may turn out to be tokenistic or merely symbolic. Engagement strategies that serve the primary purpose of granting legitimacy to decisions that experts and other elites have taken would be highly problematic, not only in that they reduce trust in public engagement [27], but also in that they are disrespectful of the stakeholders and publics that participated in such engagement.…”
Section: Exploring the 'Ethical Moment'mentioning
confidence: 99%
“…Deliberative approaches to bioethical issues, generally, and to biobanking, specifically, are burgeoning (Abelson, et. al., 2013;Avard et. al., 2009;O'Doherty & Burgess, 2009).…”
Section: The Michigan Biotrust For Health: Ripe For Deliberationmentioning
confidence: 99%